Investigating the Interaction Between Prosody and Pragmatics Quantitatively: A Case Study of the Chinese Discourse Marker ni zhidao (“You Know”) - Shan, Yi (Frontiers in Psychology, 2021)
This study briefly describes the prosodic and pragmatic characteristics of the discourse marker ni zhidao (‘you know’) in spoken Chinese, and it mainly explores the interaction between its prosody and pragmatics using instrumental methods. This is the first attempt to use acoustical and statistical analysis to examine the prosodic parameters and prosody-pragmatics interaction of Chinese discourse markers. The corpus includes a 100-hour recorded interview, in which 490 discourse marker tokens of ni zhidao were found. Ni zhidao mainly fulfilled the pragmatic functions of initiating a topic (by grabbing/taking over the turn) when occurring utterance-initially, of holding the floor when appearing within clauses, of marking coherence when making its presence between clauses, and of projecting attitudes and feelings when showing up utterance-finally. The acoustical and statistical analysis of the performances of ni zhidao in these four functions showed that its prosodic features, including duration, tempo, prepause, postpause, F0, and intensity, significantly related to and thus implied its pragmatic functions, that the interaction between its prosody and pragmatics can be modeled statistically, and that the prosody-pragmatics model can be used to predict its pragmatic functions. These findings seem to strengthen the hypothesis that prosodic data play a role in deciphering the different pragmatic functions of ni zhidao. This study uses prosodic evidence to more objectively reveal not merely the role of ni zhidao in dynamically constructing and embodying specific contexts, but also its communicative functions and the underlying meta-pragmatic awareness behind it. Such a study, to a large extent, breaks through the limitations of traditional discourse marker research, which mainly relies on context and discourse characteristics for subjective reasoning.